Caryophyllene sesquiterpenes, chromones and 10-membered macrolides from the marine-derived fungus Pseudopestalotiopsis sp. PSU-AMF45. Issue 38 (20th September 2019) - Putra, Haryadi N.; Rukachaisirikul, Vatcharin; Saithong, Saowanit; Phongpaichit, Souwalak; Preedanon, Sita; Sakayaroj, Jariya; Hadsadee, Sarinya; Jungsuttiwong, Siriporn
Abstract: Three new caryophyllene sesquiterpenes, pestalotiopsins I–K, one new chromone, pseudopestalone, and one new 10-membered macrolide, decarestrictine Q, were isolated from the fermentation broth of the marine-derived fungus Pseudopestalotiopsis sp. PSU-AMF45 along with twelve known compounds. Their structures were identified by spectroscopic data including 1D and 2D NMR. The absolute configuration of pestalotiopsin I was assigned based on single-crystal X-ray diffraction crystallography whereas that of the secondary alcohol moiety in pestalotiopsin J was established by Mosher's method. For pseudopestalone, the absolute configuration was determined by ECD spectrum associated with TD-DFT calculation. The antimicrobial activity of the isolated compounds was evaluated. Graphical abstract: Image 1 Highlights: The fungus Pseudopestalotiopsis sp. PSU-AMF45 was isolated from an ascidian. Three caryophyllene sesquiterpenes, one chromone and one 10-membered macrolide are previously undescribed. The absolute configuration was established by X-ray crystallography, Mosher's method or ECD calculation. Secondary metabolites of the genus Pseudopestalotiopsis are reported for the first time.